Toxicity of Plant Secondary Metabolites Modulating Detoxification Genes Expression for Natural Red Palm Weevil Pesticide Development - Ahmed Mohammed AlJabr; Abid Hussain; Muhammad Rizwan-ul-Haq; Hassan Al-Ayedh (Molecules, 2017)
This study aimed to explore the larvicidal and growth-inhibiting activities, and underlying detoxification mechanism of red palm weevil against phenylpropanoids, an important class of plant secondary metabolites. Toxicity of α-asarone, eugenol, isoeugenol, methyl eugenol, methyl isoeugenol, coumarin, coumarin 6, coniferyl aldehyde, diniconazole, ethyl cinnamate, and rosmarinic acid was evaluated by incorporation into the artificial diet. All of the phenylpropanoids exhibited dose- and time-dependent insecticidal activity. Among all the tested phenylpropanoids, coumarin exhibited the highest toxicity by revealing the least LD50 value (0.672 g/L). In addition, the most toxic compound (coumarin) observed in the current study, deteriorated the growth resulting tremendous reduction (78.39%) in efficacy of conversion of digested food (ECD), and (ECI) efficacy of conversion of ingested food (70.04%) of tenth-instar red palm weevil larvae. The energy-deficient red palm weevil larvae through their intrinsic abilities showed enhanced response to their digestibility resulting 27.78% increase in approximate digestibility (AD) compared to control larvae. The detoxification response of Rhynchophorus ferrugineus larvae determined by the quantitative expression of cytochrome P450, esterases, and glutathione S-transferase revealed enhanced expression among moderately toxic and ineffective compounds. These genes especially cytochrome P450 and GST detoxify the target compounds by enhancing their solubility that leads rapid excretion and degradation resulting low toxicity towards red palm weevil larvae. On the other hand, the most toxic (coumarin) silenced the genes involved in the red palm weevil detoxification mechanism. Based on the toxicity, growth retarding, and masking detoxification activities, coumarin could be a useful future natural red palm weevil-controlling agent.